Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Certainly! Let's analyze the given expression [tex]\((x-p)(x-q)\)[/tex].
To solve for [tex]\(x\)[/tex], we need to understand the concept being illustrated here. This expression is a product of two binomials. For a product of two quantities to be zero, at least one of the quantities must be zero. Mathematically, this concept is captured by the Zero Product Property.
Step-by-Step Solution:
1. Consider the product [tex]\((x-p)(x-q) = 0\)[/tex].
2. According to the Zero Product Property, if the product of two terms is zero, then at least one of the terms must be zero.
3. This gives us two possible equations:
- [tex]\(x - p = 0\)[/tex]
- [tex]\(x - q = 0\)[/tex]
4. Solving these equations individually:
- From [tex]\(x - p = 0\)[/tex], we get [tex]\(x = p\)[/tex].
- From [tex]\(x - q = 0\)[/tex], we get [tex]\(x = q\)[/tex].
So, the solutions to the equation [tex]\((x-p)(x-q) = 0\)[/tex] are [tex]\(x = p\)[/tex] or [tex]\(x = q\)[/tex].
Therefore, [tex]\((x-p)(x-q) \rightarrow x=p \text{ or } x=q\)[/tex] illustrates the Zero Product Property.
Type your answer in the box.
To solve for [tex]\(x\)[/tex], we need to understand the concept being illustrated here. This expression is a product of two binomials. For a product of two quantities to be zero, at least one of the quantities must be zero. Mathematically, this concept is captured by the Zero Product Property.
Step-by-Step Solution:
1. Consider the product [tex]\((x-p)(x-q) = 0\)[/tex].
2. According to the Zero Product Property, if the product of two terms is zero, then at least one of the terms must be zero.
3. This gives us two possible equations:
- [tex]\(x - p = 0\)[/tex]
- [tex]\(x - q = 0\)[/tex]
4. Solving these equations individually:
- From [tex]\(x - p = 0\)[/tex], we get [tex]\(x = p\)[/tex].
- From [tex]\(x - q = 0\)[/tex], we get [tex]\(x = q\)[/tex].
So, the solutions to the equation [tex]\((x-p)(x-q) = 0\)[/tex] are [tex]\(x = p\)[/tex] or [tex]\(x = q\)[/tex].
Therefore, [tex]\((x-p)(x-q) \rightarrow x=p \text{ or } x=q\)[/tex] illustrates the Zero Product Property.
Type your answer in the box.
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.